The Principles Of Traditionalism And Renewal In The Work Of Muhyi And His Contemporaries (Eurasian Journal of Learning and Academic Teaching, 2023)
This article was written about the most used genre in the work of poets living in the Kokand literary environment of the studied period is the ghazal genre. In their ghazals, they mainly glorified feelings such as love, loyalty, fidelity, friendship, kindness, patriotism. In the ghazals of poets, the theme of love is especially deeply interpreted. As you know, in classical literature, two types of Ishq are considered – figurative and real Ishq. Poets made extensive use of both of these types of work in their lyrics.